SUSTAINABLE PERFORMANCE INDICATORS IN IMPROVING SUSTAINABLE PERFORMANCE IN URBAN DRINKING WATER SERVICES - Meilan Agustin; Parwadi Moengin; Emelia Sari; Astri Rinanti; Feybi A. Goni; M.Y. Abu (Universitas Trisakti, 2025)
Although 71% of the Earth is covered by water, only 1% is accessible for human use, creating increasing challenges in urban areas. Population growth, urbanization, climate change, and pollution intensify the difficulty of providing safe drinking water. While SDG 6 highlights universal access and sustainable management, urban water services face not only supply and demand gaps but also social equity, service reliability, and environmental sustainability. Addressing these requires integrated approaches that balance quality, quantity, efficiency, and long-term resilience. Aim: This study aimed to determine the indicators of sustainable performance in drinking water services in urban areas. Methodology and results: First, a systematic literature review was conducted using Scopus-indexed publications from 2013–2023, comprising 437 journal articles and 66 conference papers, to analyze themes and content. Next, a general urban water management model was identified, followed by the definition of sustainability factors and perspectives for urban water services. Finally, sustainable performance indicators were developed for each perspective to ensure comprehensive evaluation and implementation. Conclusion, significance, and impact study: The study identifies 20 economic, 8 environmental, and 18 social performance indicators. They measure affordability, continuity, quantity, carbon emissions, pollution, behavior, accessibility, and policy, evaluating urban water services sustainability and efficiency comprehensively.